Analisis globalisasi terhadap keamanan negara: (studi kasus : penyalahgunaan izin tinggal WNA TKA non-prosedural di Bali tahun 2022-2023) - Ni Luh Putu Cintya Devi; I Made Anom Wiranata; Gek Dian Kencana Asih (Economic Military and Geographically Business Review, 2023)
The flow of globalization is one form of contemporary development. Globalization provides many benefits for human life globally. One perceived benefit of globalization is the ease of information and technology that is widely spread on the global stage. Sophisticated technology is in the spotlight in connecting the international community easily without restrictions. Traveling from one country to another has become a trend in the current era. Foreign tourists take advantage of easy access to information and technology when visiting various parts of the country. However, with the benefits of globalization, it is not uncommon to find violations committed by international tourists when visiting a country. One of them occurred in Indonesia, especially in Bali, where Non-Procedural Workers (Illegal Workers) were found to be abusing residence permits in 2022-2023. This research aims to analyze the development of globalization with the emergence of non-traditional threats through policies formed to maintain a country's national security using descriptive qualitative methods. In analyzing the case, the author uses international security theory. In the case of violations committed by foreigners, they threaten the stability of a country's national security, which can lead to non-traditional threats to international security. In handling violations, actors within the country provide strict sanctions given by a country's immigration authorities in the form of deportation. The role of immigration in carrying out its duties in monitoring the inflow and outflow of foreigners cannot be separated from the role of the actors involved, such as the implementation of TIMPORA, the police, and the role of the community.